Contribuitions of extension at the Federal University of Espírito Santo from the perspective of the People Axis of the 2030 Agenda - Gomes da Silva, Elaine Cristina; Pereira Aguiar Cunha de Almeida, Felipe; Gonçalves de Moura, Bianca; Pavuna da Silva, Allan; Teodoro Lobato, Lucas José (Guará Journal, 2025)
The 2030 Agenda is a global action plan proposed to member countries by the United Nations (UN), made up of 169 integrated goals distributed in 17 Sustainable Development Goals (SDGs) that act on five axes: People, Planet, Peace, Prosperity and Partnership, with the aim of minimizing problems faced by the world today that hinder the sustainability of the planet. Faced with the challenges of implementing this Agenda, the role of universities stands out, as they play an important role in shaping opinions and professionals who will solve society’s demands. The aim of this study was therefore to investigate the extension activities carried out at the Federal University of Espírito Santo (Ufes) in relation to the SDGs of the People Hub, following the creation of the 2030 Agenda. This case study was based on the extension activities registered with the Pro-Rectory of Extension (PROEX) between 2016 and 2023. The results showed that there were 1,360 different activities related to the six SDGs of the People Hub, with SDG 4 and SDG 3, respectively, having the highest number of activities. Finally, although these activities were classified according to SDG in this study, it can be seen that the implementation of the SDGs at Ufes is still in its infancy.